2013
DOI: 10.1103/physrevd.87.063527
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints from supernovae Ia and gamma-ray bursts on a clumpy universe

Abstract: The luminosity distance describing the effect of local inhomogeneities in the propagation of light proposed by Zeldovich-Kantowski-Dyer-Roeder (ZKDR) is tested with two probes for two distinct ranges of redshifts: supernovae Ia (SNe Ia) in 0.015 ≤ z ≤ 1.414 and gamma-ray bursts (GRBs) in 1.547 ≤ z ≤ 3.57. Our analysis is performed by a Markov Chain Monte Carlo (MCMC) code that allows us to constrain the matter density parameter Ωm as well as the smoothness parameter α that measures the inhomogeneous-homogeneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
1
11
3
Order By: Relevance
“…It is suggested that a Universe composed only by homogeneously distributed matter is strongly favored by GRB observations. This is greatly different from what was obtained in previous works [32,33].…”
Section: B Long Gamma-ray Burstscontrasting
confidence: 99%
See 4 more Smart Citations
“…It is suggested that a Universe composed only by homogeneously distributed matter is strongly favored by GRB observations. This is greatly different from what was obtained in previous works [32,33].…”
Section: B Long Gamma-ray Burstscontrasting
confidence: 99%
“…This is completely different from what was obtained in Ref. [33]. Finally, we perform a joint analysis which provides good constraints on both model parameters.…”
Section: Conclusion and Discussioncontrasting
confidence: 57%
See 3 more Smart Citations